Shrimp cultivation and coastal livelihood: a focus on Bangladesh coastal vulnerability - Karim, A.H.M Zehadul; Mustari, Sohela (Canadian Center of Science and Education, 2015)
Shrimp cultivation has developed rapidly in coastal Bangladesh. Secondary literature provides evidence that to afford an alternative way of livelihood for the locals, shrimp cultivation has been extended widely throughout the coastal areas of Bangladesh. But, the extension of shrimp farming is unable to create work opportunity for the locals in the true sense. In this research, by using a household survey, to know their basic demographic information, it is revealed that though 80% of the household heads main occupation is fishing and related works only 0.71% of their main source of fishing is shrimp farm. Moreover, in-depth interviews and focus group discussions disclose that shrimp cultivation of this village is controlled and retained by the rich and outside investors, not by the poor locals. This research also discovers that man-made disasters along with natural disasters are equally responsible for generating vulnerability from shrimp cultivation.